2003
DOI: 10.1007/s00423-003-0397-z
|View full text |Cite
|
Sign up to set email alerts
|

Echinococcus granulosus infection: the challenge of surgical treatment

Abstract: Cystectomy and omentoplasty for CE should be the standard surgical procedure because it is safe, simple, and effective and meets all criteria of surgical treatment for hydatid disease: entire elimination of the parasite, no intraoperative spillage especially by using a cone, and saving healthy tissue. Pericystectomy should be used for peripherally located liver cysts that are surrounded by parenchyma only partially. Ultrasonic classification of the parasitic lesion should be used as a guideline for therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
122
0
8

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(131 citation statements)
references
References 73 publications
(99 reference statements)
1
122
0
8
Order By: Relevance
“…These procedures eventually eradicate the entire parasite, resulting in a complete cure without recurrence. However, the technical procedures remain controversial (27) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These procedures eventually eradicate the entire parasite, resulting in a complete cure without recurrence. However, the technical procedures remain controversial (27) .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, mortality and morbidity were remarkably higher with the radical procedures than with the conservative surgical option. A previous meta-analysis reported rates for mortality of 2%, morbidity of 23%, and recurrence of 10.4% with radical operations (27) , and the authors suggested that procedures that remove the parasite and retain the pericyst are easier to conduct than radical methods. Moreover, many surgeons consider that the radical methods are too radical for a benign disease (11) .…”
Section: Discussionmentioning
confidence: 99%
“…These procedures are eventually targeting the entire eradication of the parasite for complete cure without recurrence. However, the technical procedures are still a matter of controversy [27].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many surgeons considered these radical methods are too radical for a benign disease [11]. The meta-analysis done by other investigators revealed a mortality of 2%, morbidity of 23% and recurrence rate of 10.4% for such radical types of operations [27]. These authors considered the procedures that remove the parasite and keep the pericyst are easier to carry out than radical ones.…”
Section: Discussionmentioning
confidence: 99%
“…This approach is becoming more widely used and actually PAIR plus drug therapy represents the first recommended approach, mainly for uncomplicated cysts with a limited number of daughter cysts, with diameter until 7-8cm, for the reported low complication rate and because it don't hamper surgical treatment of refractory cysts. The role of surgery is progressively narrowing, being confined to the most complicated cases that require more surgical expertise [6][7][8][9]. Surgery needs to be effective to inactivate scolices, preventing recurrence and spillage into the abdomen and to obliterate the residual cavity in order to decrease the rate of post-operative complications.…”
Section: Introductionmentioning
confidence: 99%